Estudio constitucional doctrinario y jurídico del código de trabajo referente al contrato de trabajo a tiempo fijo - Perez Zambrano, Edith Esperanza (2015)
Work is a right and a social duty, the modern conception of society and of the right places man in society and imposes duties and granted rights derived each other of their social nature : society has the right to require its members to exercise a useful and honest activity , and man in turn has the right to claim society the existence of a security consistent with the dignity of the human person . The duration of employment contracts has been a very important element of discussion on labor issues , the solution was no longer offered by the will of the contracting parties , due to their unequal status to be assumed, at least in its minimum limits , by the Ecuadorian labor law . Given the problems described above decided preparing this research work entitled " Doctrinal STUDY CONSTITUTIONAL AND LEGAL CODE REFERENCE WORK LABOUR CONTRACT TIME FIXED " in which I make a doctrinal and legal analysis of the issues raised , being able to demonstrate the failure of law and the urgent need to establish a procedure to regulate the employment contract at a fixed time, in order not to undermine the worker's right to job security . Therefore in this work the theoretical arguments are collected, results of field research , in which analysis shows the need for a special procedure for the employment contract at fixed time , and this is the main idea of my thesis work with I hope it helps to solve this problem.